Small RNA in situ hybridization in Caenorhabditis elegans, combined with RNA-seq, identifies germline-enriched microRNAs() - McEwen, Tamara J. (Dev Biol, 2016)
Over four hundred different microRNAs (miRNAs) have been identified in the genome of the model organism the nematode Caenorhabditis elegans. As the germline is dedicated to the preservation of each species, and almost half of all the cells in an adult nematode are germline, it is likely that regulatory miRNAs are important for germline development and maintenance. In C. elegans the miR35 family has strong maternal effects, contributing to normal embryogenesis and to adult fecundity. To determine whether any particular miRNAs are greatly enriched in the C. elegans germline we used RNA-seq to compare the miRNA populations in several germline-defective strains of adult C. elegans worms, including glp-4(germline proliferation-4), glh-1(germline helicase-1) and dcr-1(dicer-1). Statistical analyses of RNA-seq comparisons identified 13 miRNAs that are germline-enriched, including seven members of the well-studied miR35 family that were reduced as much as 1000-fold in TaqMan qRT PCR miRNA assays. Along with the miR35s, six others: miR-56 (a member of the miR51 family),−70, −244, −260 , −788 and −4813, none of which previously considered as such, were also identified by RNA-seq as germline-enriched candidates. We went on to develop a successful miRNA in situ hybridization protocol for C. elegans, revealing miR35s specifically concentrate during oogenesis in the pachytene region of the gonad, and persist throughout early embryogenesis, while in adult animals neither let-7 nor miR-228 has a germline-bias.